Oudano as praxis: archives, audiotopias and movements - Sakaria, Nashilongweshipwe (School of Dance, 2023)
Several Namibian studies have looked at Oudano as an expansive Oshiwambo and Rukwangali concept that implies utterances of play, performance, and performativity in spheres of culture, sports, religion, and politics. This thesis offers experiments that explore the critical usefulness of Oudano. I embark on these experiments in a deliberately undisciplined way, crossing media, time periods, ethnicities, geographies, and emphasising embodiment and mobility. In the process I show how Oudano is a practice of critical orientation in various respects, by looking at cultural work that questions institutional constraints and exclusions. This study departs from the disjuncture between cultural work that is authorised by hegemonic national heritage discourse and unauthorised cultural work in action, offering other ways of knowing with different aims that slide into the cracks, between and outside of power. The disjuncture endorses structural disparities that are a direct result of a cultural hegemony, its aims and exertion of power. I was motivated by a deep anxiety caused by Namibia's post-apartheid dominant epistemologies that fundamentally exclude indigenous and subaltern methods of knowledge production. This thesis was aimed at finding a range of conceptual and methodological approaches for critical consciousness and radical imagination across place and time. I made a choice to focus on a set of ‘unrelated objects' which include my cultural practices and those of other cultural workers in Namibia. African queer and performance theories are interfaced with Oudano to demonstrate the relatedness of these objects. The objects gathered and analysed in this study were given status of archive to point to their role of memory making in social and cultural movements. Methodologically, I relied on Archival research and Practice-as-Research (P-aR) to interweave my (performance and curatorial) practice and historical research. The thesis is a collection of six papers divided in two movements which offer specific insights about the various objects of analysis. These objects include lino-cut prints, rock art, colonial photography and sonic archives, performance art, museum theatre, site-related performance, jazz, struggle music, HipHop, Kwaito, Shambo, documentary film, orature, oral history, protest action, as well as curatorial practice. Given its epistemic potential, Oudano is a generative approach of decolonising our understandings of performance cultures. Through close reading and listening to works of Oudano produced in Namibia, I demonstrate how people have historically practiced Oudano to construct audiotopic imaginations and build social movements. While this offers decolonial lessons for both performance and archivality, Oudano is an indigenous framework of preserving and queering knowledge. In that sense, a queer understanding of Oudano exceeds geo-political and ethnic borders, signifying how it has historically accompanied historic migrations of artists and material culture, as well as activists and non-normative ideas. By reading Oudano across time allowed this study to interrupt periodisation, showing Oudano's potential as a trans-temporal practice. Overall, this study contributes to the long- existing gap of performance studies as a field in Namibian studies. It pays attention to overlooked archives of cultural work, most of which have hardly received any scholarly attention. The thesis exceeds my disciplinary training of drama and theatre, demonstrating Oudano as an intellectual praxis that is leaky, slippery, and undisciplined.